Estimation of Alignment and Transverse Load in Multi-Bearing Rotor System - Tom J. Chalko; Dong-Xu Li (International Journal of Rotating Machinery)
The paper presents a method for estimation of a multi-bearing machine alignment on the basis of measured eccentricities of the shaft in machine bearings. The method uses a linear FEM model of the rotor and the non-linear models of machine bearings. In the presented example, the non-linear models of hydrodynamic bearings are used, but it is shown, that the method could be easily applied to other types of bearings. In addition to the alignment estimation, the method allows to estimate the unknown static load in the transverse direction, reduced to the equivalent load at one or two selected nodes on the shaft. Verification of the method is presented using the model of a machine with vertical shaft supported in three pressurised hydrodynamic bearings. The method is suitable for monitoring of alignment and transverse load during the machine operation.